Four new species of Empoasca (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) and one new record from China - Liu, Yang; Qin, Dao-Zheng; Fletcher, Murray J.; Zhang, Ya-Lin (Zootaxa, 2011)
Four new species of Empoasca (Empoasca Walsh) are described from China: E. (E.) dahaopingensis Qin & Liu, E. (E.) gutianensis Zhang & Liu, E. (E.) lijiangensis Liu, and E. (E.) apibicruris Liu spp. nov. In addition, E. (E.) dymarka Dworakowska, 1984, is recorded from China for the first time. E. (E.) apibicruris, and E. (E.) dymarka are placed in the Empoasca albipennis group with E. (E.) albipennis Dworakowsa, 1977. Habitus photos and illustrations of the male genitalia of the new species are provided.